A systematic review of metabolic side effects related to the use of antipsychotic drugs in dementia. (January 2014) - Atti, A.R.; Ferrari Gozzi, B.; Zuliani, G.; Bernabei, V.; Scudellari, P.; Berardi, D.; De Ronchi, D.; Tarricone, I.; Menchetti, M.
ABSTRACT Background: In clinical practice, Second Generation Antipsychotics (SGAs) are often used as first-line treatment for the Behavioral and Psychological Symptoms of Dementia (BPSD) in older adults due to their fewer neurological adverse events and similar effectiveness compared with First Generation Antipsychotics (FGAs). SGAs, however, are associated with more severe metabolic side effects (weight gain, hyperglycemia, diabetes risk, and hyperlipidemia) than FGAs are. In general, older patients, especially those affected by dementia, are at increased risk for malnutrition, and tend to have lower basal metabolism and reduced liver and kidney function. However, little is known about the metabolic side effects of antipsychotic drugs in this population. Methods: A comprehensive review of the literature published between January 1996 and December 2012 investigating the metabolic side effects related to FGAs and SGAs use in old patients affected by dementia. Results: Antipsychotic drugs currently used to treat BPSD in subjects with mild to moderate dementia are associated with weight gain. Currently, there are insufficient data to support a causal relationship between the use of FGAs and SGAs and changes in glucose homeostasis or lipid metabolism in older persons affected by severe dementia (MMSE <14). Conclusion: A possible association between antipsychotic drugs use and weight gain might exist, in particular in subjects with mild to moderate dementia whereas no significant effects are demonstrated regarding glucose homeostasis and lipid metabolism. The antipsychotic drugs potential for causing metabolic abnormalities in older patients requires further specifically designed studies. Clinicians must be aware of this possibility even if the shorter periods of treatment administered in late-life might not be as harmful as it is in younger individuals.